Audit Fees Determinants: A Study on the Impact of Key Audit Matters Reporting and other Factors - et.al, Zuaini Ishak (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Knowledge is now an essential source of competitive advantage. Itenhanceseconomic growth and increasescorporate value. In the field of auditing, authority was aware of the need for improved reporting and thus has issued a brand newstandard related to auditor's report.While the new report is expected to enhanceaudit reporting and improve the quality of audit, the move may also increasethe audit costs as auditorsnow needto expandtheir efforts. We analyzed 261 companies listed on Bursa Malaysia and the results indicate that the requirement to improve auditor's communication through enhanced reporting does not influence audit fees. Instead, the study suggests that the company size, poor financial performance and liquidity issue are key determinants of audit fees. The two world's largest audit firms, i.e., PWC and KPMG, are found to charge higher fees than others, possibly for the brand name. This study informs regulators of the influence of the new requirement on audit output costs.It also offers insight into the main drivers for audit pricing following the current reporting requirement.